Effectiveness of the National Health Social Security System in Ensuring Public Welfare in Indonesia - Hutagalung, Tiur Hasmida; Sara, Rineke (Ridwan Institute, 2025)
The state offers its inhabitants social health security as a type of legal protection to guarantee their welfare and access to quality medical care. Law Number 40 of 2004 about the National Social Security System (SJSN) and Law Number 24 of 2011 concerning the Social Security Administering Body (BPJS) are two of the legislation that govern Indonesia's social health security system. This rule highlights that all citizens are entitled to equitable and fair social protection in the health sector. However, in its implementation, various challenges arise, such as the BPJS Kesehatan budget deficit, limited access to health services in remote areas, and participant compliance in paying contributions. Therefore, a study of the legal concept in the regulation of national social health security is critical to understand the basic principles underlying this system and the effectiveness of its regulation in practice. This study uses a normative juridical method, which focuses on the laws and regulations governing national social health security in Indonesia. The approaches used include a statute approach to analyze applicable legal norms, a conceptual approach to explore the legal concepts underlying the social health security system, and a historical approach to see the development of related regulations. With this method, the study examines the legal basis, legal principles underlying national social health security, and challenges in implementing existing regulations. This study is expected to provide a deeper understanding of the legal aspects of regulating social health security in Indonesia and recommend strengthening future policies.